Switching behaviour of individual Ag-TCNQ nanowires: an in situ transmission electron microscopy study. (13th September 2016) - Ran, Ke; Rösner, Benedikt; Butz, Benjamin; Fink, Rainer H; Spiecker, Erdmann
Abstract: The organic semiconductor silver-tetracyanoquinodimethane (Ag-TCNQ) exhibits electrical switching and memory characteristics. Employing a scanning tunnelling microscopy setup inside a transmission electron microscope, the switching behaviour of individual Ag-TCNQ nanowires (NWs) is investigated in detail. For a large number of NWs, the switching between a high (OFF) and a low (ON) resistance state was successfully stimulated by negative bias sweeps. Fitting the experimental I – V curves with a Schottky emission function makes the switching features prominent and thus enables a direct evaluation of the switching process. A memory cycle including writing, reading and erasing features is demonstrated at an individual NW. Moreover, electronic failure mechanisms due to Joule heating are discussed. These findings have a significant impact on our understanding of the switching behaviour of Ag-TCNQ.